Descripción del Injerto de púa en Campo de Persea americana Mill var. Hass en Ucupe Zaña-Lambayeque - Cotrina Tirado, Erika Noravita (2017)
The present work was carried out with the objective of describing the graft of persea americana mill var. Hass in ucupe Zaña-Lambayeque. In order to do this, the description of the initial tasks related to nursery propagation was made. Until the definitive field stage. The description consisted of observing in a clear and precise way all the steps of the graft, cutting, mooring and the tasks that continue after grafting for the care of it. The field grafting procedure of Persea americana Mill var. Hass seeks to improve the climatic and physiological conditions of the plant in order to receive the new bud in the best possible way; which includes some very important agronomic work such as irrigation, fertilization and phytosanitary control. The seedling used was of zutano variety; variety very resistant to water stress conditions. For this the process of selection of buds and disinfection was performed and after being 15 days in the field will proceed to perform the graft. The type of graft used is the double-barrel gusset. The average production of avocado variety Hass in the area ranges between 12tn / ha but with this new proposal of grafting in the field is looking to have plants more robust and durable so that they continue to produce longer and in greater quantities. The results are obtained in response to% Yolk Yield, Vigorosity, Incidence of insect pests